(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article analyzes the content of the concept of a village, the history of its formation and stages of development. The village is considered an important component of human society in socio-economic, cultural and geographical terms. The article also discusses in detail the factors that influenced the formation of rural areas, including natural and geographical conditions, demographic situation, economic activity and the role of social institutions. The author analyzed the changes in the village in different periods based on historical processes and also touched on its modern significance. This article is an important scientific source for understanding the development of the village and its place in society